Peripheral and Thymic Foxp3+ Regulatory T Cells in Search of Origin, Distinction, and Function - Dhamne, Chetan; Chung, Yeonseok; Alousi, Amin M.; Cooper, Laurence J.; Tran, Dat Q. (Frontiers in Immunology, 2013)
Over the past decade, much has been learnt and much more to discover about Foxp3+ regulatory T cells (Tregs). Initially, it was thought that Tregs were a unique entity that originates in the thymus. It is now recognized that there is a fraternal twin sibling that is generated in the periphery. The difficulty is in the distinction between these two subsets. The ability to detect, monitor and analyze these two subsets in health and disease will provide invaluable insights into their functions and purposes. The plasticity and mechanisms of action can be unique and not overlapping within these subsets. Therefore, the therapeutic targeting of a particular subset of Tregs might be more efficacious. In the past couple of years, a vast amount of data have provided a better understanding of the cellular and molecular components essential for their development and stability. Many studies are implicating their preferential involvement in certain diseases and immunologic tolerance. However, it remains controversial as to whether any phenotypic markers have been identified that can differentiate thymic versus peripheral Tregs. This review will address the validity and controversy regarding Helios, Lap/Garp and Neuropilin-1 as markers of thymic Tregs. It also will discuss updated information on distinguishing features of these two subsets and their critical roles in maternal-fetal tolerance and transplantation.